Relationship between compressive and splitting tensile strength of geopolymer concrete - Anuradha, R.; Sreevidya, V.; Venkatasubramani, R.; Rangan, B. Vijaya (The Associated Cement Companies Limited, 2011)
This experimental study was undertaken to identify the relationship between compressive strength and splitting tensile strength of geopolymer concrete. The study examines existing, commonly accepted 0.5 power relationship between compressive strength (CS) and splitting tensile strength (STS) in cement concrete and investigates its applicability to geoploymer concretes. Two types of systems were studied; one using ASTM class F flyash in place of cement and the other replacing sand with manufactured -sand. Different grades of geopolymer concrete mixes were compared with conventional mixes. The test result suggested that the 0.5 power relationship for conventional concrete was not valid for GPCs. The study proposes alternative relations for this family of materials.